2022
DOI: 10.3389/fcvm.2022.857922
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model involving serum uric acid, C-reactive protein, diabetes, hypercholesteremia, multiple lesions for restenosis risk in everolimus-eluting stent-treated coronary heart disease patients

Abstract: PurposeAs a second-generation drug-eluting stent, the restenosis risk factors of the everolimus-eluting stent (EES) lack sufficient evidence. Therefore, the study investigated the in-stent restenosis occurrence and its predictive factors among patients with coronary heart disease (CHD) who underwent percutaneous coronary intervention (PCI) with EES.Materials and methodsTotally, 235 patients with CHD who underwent PCI with EES were included. At 1 year post PCI with EES (or earlier if clinically indicated), coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Physicians consider a combination of these factors, but because each patient's situation is unique, prognosis assessment needs to be individualized and closely monitored. In the past, many studies have said that [5] [6] changes in serum uric acid (SUA) levels are independently related to the incidence rate and mortality of cardiovascular diseases, and some studies have also shown that [7] Hyperuricemia (HUA) is associated with poor prognosis of elderly CHF, and the risk of rehospitalization of patients with HUA is significantly increased. Moreover, SUA can also cause inflammatory and oxidative stress reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians consider a combination of these factors, but because each patient's situation is unique, prognosis assessment needs to be individualized and closely monitored. In the past, many studies have said that [5] [6] changes in serum uric acid (SUA) levels are independently related to the incidence rate and mortality of cardiovascular diseases, and some studies have also shown that [7] Hyperuricemia (HUA) is associated with poor prognosis of elderly CHF, and the risk of rehospitalization of patients with HUA is significantly increased. Moreover, SUA can also cause inflammatory and oxidative stress reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SUA has been demonstrated to be an independently related marker for an elevated risk of stent restenosis after PCI. When combined with diabetes, hypercholesterolemia, hs-CRP and lesions in multiple target regions, SUA can form a prediction model for the risk of in-stent restenosis in individuals with CAD undergoing PCI [ 55 ]. Likewise, SUA has been demonstrated to be an independently predictive risk marker for MACE and the presence of multiple coronary lesions 1–3 years after PCI in individuals with ACS and hypertension [ 56 ].…”
Section: Introductionmentioning
confidence: 99%